Autoimmune hepatitis after COVID-19 vaccination - Zheng, Han; Zhang, Ting; Xu, Yiyao; Lu, Xin; Sang, Xinting (Frontiers in Immunology, 2022)
Vaccination is one of the most vigorous ways to intervene the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) catastrophe. Autoimmune hepatitis (AIH) after coronavirus disease 2019 (COVID-19) vaccination have been increasingly reported. Twenty-seven cases of AIH are summarized here as emerging evidence of autoimmune reactions in response to various COVID-19 vaccines, including patients with special disease backgrounds such as primary sclerosing cholangitis (PSC), liver transplantation and previous hepatitis C virus (HCV) treatment. Molecular mimicry, adjuvants, epitope spreading, bystander activation, X chromosome and sceptical hepatotropism of SARS-CoV-2 may account for such autoimmune phenomena to some extent. Immunosuppressive corticosteroids perform well with or without azathioprine in such post-COVID-19-vaccination AIH. However, what needs to be further confirmed are certain answer to exact mechanism riddle as well as causality establishment.